2020
DOI: 10.12775/jehs.2020.10.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate fat diet

Abstract: Aim. To determine the main factors of inadequate fat diet (IAFD) and indicate the ways of their change. Methods. Analysis and generalization of existing scientific literature data and the results of our own research. Results. The following factors of IAFD have been identified: 1) excess fat in the diet; 2) an excess of palmitic acid in dietary fats; 3) an excess of linoleic acid in dietary fats; 4) consumption of thermoperoxide fats; 5) deficiency of ω-3 polyunsaturated fatty acids (PUFA). Conclusion. IAFD is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…It has been established that excessive consumption of fats causes the activation of free radical oxidation of unsaturated fatty acids with the formation of toxic peroxidation products (Levitsky, Egorov, Lapinskaya et al, 2020).…”
Section: медицинаmentioning
confidence: 99%
“…It has been established that excessive consumption of fats causes the activation of free radical oxidation of unsaturated fatty acids with the formation of toxic peroxidation products (Levitsky, Egorov, Lapinskaya et al, 2020).…”
Section: медицинаmentioning
confidence: 99%
“…In our previous works [11,12], it was shown that in the composition of lipids of an animal organism in the conditions of keeping animals on a fat-free diet, such fatty acids (for example, PUFA) are also determined, which, as a rule, are not formed in the cells of the body according to the above scheme formation of energy fatty acids [13,[20][21][22].…”
Section: Synthase Fatty Acidsmentioning
confidence: 99%
“…First, the presence of two double bonds (С18:2, ω-6) in the linoleic acid molecule determines its instability during storage and thermal cooking due to peroxidation processes [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…And finally, fifthly, linoleic acid in the body is transformed into arachidonic acid (C20:4, ω-6), from which pro-inflammatory eicosanoids are formed [1,3].…”
Section: Introductionmentioning
confidence: 99%